2009
DOI: 10.1007/s12630-009-9149-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase inhibition attenuates neuropathic pain but lacks pre-emptive effects in rats

Abstract: Purpose There is evidence that cyclic adenosine monophosphate (cAMP) transduction is involved in nociceptive processing. We previously showed that intrathecal injection of an adenylate cyclase inhibitor attenuated tactile allodynia caused by partial sciatic nerve ligation (PSNL) in rats. The present study investigates the pre-emptive effects of spinal cAMP transduction on nociceptive processing in a chronic neuropathic pain model. Methods Intrathecal catheterization and PSNL were performed in male Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…cAMP signalling has been primarily implicated in the development of pain hypersensitivity in an inflammatory state as many inflammatory mediators signal through G protein-coupled receptors that are coupled with G proteins that activate (Gs) adenylate cyclase, whilst other inflammatory mediators may cause an increase in intracellular calcium that activates calcium-sensitive adenylate cyclases. Pharmacological and genetic evidences also suggest a role for cAMP in the development of mechanical allodynia in rodent models of neuropathic pain [ 18 , 22 , 23 ]. For example, the development of mechanical allodynia is severely impaired in models of neuropathic pain in mice deficient for adenylate cyclase 5 [ 18 ].…”
Section: Peripheral Mechanisms Linked To Mechanical Allodyniamentioning
confidence: 99%
“…cAMP signalling has been primarily implicated in the development of pain hypersensitivity in an inflammatory state as many inflammatory mediators signal through G protein-coupled receptors that are coupled with G proteins that activate (Gs) adenylate cyclase, whilst other inflammatory mediators may cause an increase in intracellular calcium that activates calcium-sensitive adenylate cyclases. Pharmacological and genetic evidences also suggest a role for cAMP in the development of mechanical allodynia in rodent models of neuropathic pain [ 18 , 22 , 23 ]. For example, the development of mechanical allodynia is severely impaired in models of neuropathic pain in mice deficient for adenylate cyclase 5 [ 18 ].…”
Section: Peripheral Mechanisms Linked To Mechanical Allodyniamentioning
confidence: 99%
“…Numerous studies have shown that activation of the spinal PKA pathway contributes to neuropathic and inflammatory pain (Wang et al. , 2006; Liou et al. , 2007, 2009; Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of analgesia seen during the initial phases after CFA administration (24-48 h), could be due the deferred hypertrophy of adenylyl cyclases after tissue injury, or the delayed role of adenylyl cyclases in enhanced transcription of pro-inflammatory molecules, taking several days to manifest (Tarnawski et al, 2018). The initial change in mechanical thresholds seen at 3 h post-CFA was surprising, as a previous study failed to demonstrate a pre-emptive effect in a rodent model of neuropathic pain with adenylate cyclase inhibitor administered before injury (Liou et al, 2009). Another previous study using the AC1-specific inhibitor NB001 indicates that inhibition of hyperalgesia after CFA administration was seen 3 days after inoculation (Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 95%